Arginase expression impedes the resolution of intestinal inflammation by altering the fecal microbiome and the metabolome - Baier, Julia; Gänsbauer, Maximilian; Giessler, Claudia; Arnold, Harald; Muske, Mercedes; Schleicher, Ulrike; Lukassen, Sören; Ekici, Arif Bülent; Rauh, Manfred; Daniel, Christoph; Hartmann, Arndt; Schmid, Benjamin; et al. (Journal of Clinical Investigation, 2020)
Arginase 1 (Arg1), which converts L-arginine into ornithine and urea, exerts pleiotropic immunoregulatory effects. However, the function of Arg1 in inflammatory bowel disease (IBD) remains poorly characterized. Here, we found that Arg1 expression correlated with the degree of inflammation in intestinal tissues from IBD patients. In mice, Arg1 was upregulated in an IL-4-/IL-13- and intestinal microbiota-dependent manner. Tie2-Cre+/-Arg1fl/fl mice lacking Arg1 in hematopoietic and endothelial cells recovered faster from experimental colitis than Arg1-expressing littermates. This correlated with decreased vessel density, compositional changes in intestinal microbiota, diminished infiltration by myeloid cells and an accumulation of intraluminal polyamines that promote epithelial healing. The pro-resolving effect of Arg1-deletion was reduced by an L-arginine-free diet, but rescued by simultaneous deletion of other L-arginine-metabolizing enzymes such as Arg2 or Nos2, demonstrating that protection from colitis requires L-arginine. Fecal microbiota transfers from Tie2-Cre+/-Arg1fl/fl mice into wild-type recipients ameliorated intestinal inflammation while transfers from wild-type littermates into Arg1-deficient mice prevented an advanced recovery from colitis. Thus, an increased availability of L-arginine as well as altered intestinal microbiota and metabolic products account for the accelerated resolution from colitis in the absence of Arg1. Consequently, the metabolism of L-arginine may serve as target for clinical intervention in IBD patients.<br

Characterization of germ cell differentiation in the male mouse through single-cell RNA sequencing - Lukassen, Sören; Bosch, Elisabeth; Ekici, Arif Bülent; Winterpacht, Andreas (Scientific Reports, 2018)
Spermatogenesis in the mouse has been extensively studied for decades. Previous methods, such as histological staining or bulk transcriptome analysis, either lacked resolution at the single-cell level or were focused on a very narrowly defined set of factors. Here, we present the first comprehensive, unbiased single-cell transcriptomic view of mouse spermatogenesis. Our single-cell RNA-seq (scRNA-seq) data on over 2,500 cells from the mouse testis improves upon stage marker detection and validation, capturing the continuity of differentiation rather than artificially chosen stages. scRNA-seq also enables the analysis of rare cell populations masked in bulk sequencing data and reveals new insights into the regulation of sex chromosomes during spermatogenesis. Our data provide the basis for further studies in the field, for the first time providing a high-resolution reference of transcriptional processes during mouse spermatogenesis.
EVALuna2:34135

Chromatin-Remodeling Factor SPOC1 Acts as a Cellular Restriction Factor against Human Cytomegalovirus by Repressing the Major Immediate Early Promoter - Reichel, Anna; Stilp, Anne-Charlotte; Scherer, Myriam; Reuter, Nina; Lukassen, Sören; Kasmapour, Bahram; Schreiner, Sabrina; Cicin-Sain, Luka; Winterpacht, Andreas; Stamminger, Thomas (Journal of Virology, 2018)
The cellular protein SPOC1 (survival time-associated PHD [plant homeodomain] finger protein in ovarian cancer 1) acts as a regulator of chromatin structure and the DNA damage response. It binds H3K4me2/3-containing chromatin and promotes DNA condensation by recruiting corepressors such as KAP-1 and H3K9 methyltransferases. Previous studies identified SPOC1 as a restriction factor against human adenovirus (HAdV) infection that is antagonized by E1B-55K/E4-orf6-dependent proteasomal degradation. Here, we demonstrate that, in contrast to HAdV-infected cells, SPOC1 is transiently upregulated during the early phase of human cytomegalovirus (HCMV) replication. We show that the expression of immediate early protein 1 (IE1) is sufficient and necessary to induce SPOC1. Additionally, we discovered that during later stages of infection, SPOC1 is downregulated in a glycogen synthase kinase 3β (GSK-3β)-dependent manner. We provide evidence that SPOC1 overexpression severely impairs HCMV replication by repressing the initiation of viral immediate early (IE) gene expression. Consistently, we observed that SPOC1-depleted primary human fibroblasts displayed an augmented initiation of viral IE gene expression. This occurs in a multiplicity of infection (MOI)-dependent manner, a defining hallmark of intrinsic immunity. Interestingly, repression requires the presence of high SPOC1 levels at the start of infection, while later upregulation had no negative impact, suggesting distinct temporal roles of SPOC1 during the HCMV replicative cycle. Mechanistically, we observed a highly specific association of SPOC1 with the major immediate early promoter (MIEP), strongly suggesting that SPOC1 inhibits HCMV replication by MIEP binding and the subsequent recruitment of heterochromatin-building factors. Thus, our data add SPOC1 as a novel factor to the endowment of a host cell to restrict cytomegalovirus infections.IMPORTANCE Accumulating evidence indicates that during millennia of coevolution, host cells have developed a sophisticated compilation of cellular factors to restrict cytomegalovirus infections. Defining this equipment is important to understand cellular barriers against viral infection and to develop strategies to utilize these factors for antiviral approaches. So far, constituents of PML nuclear bodies and interferon gamma-inducible protein 16 (IFI16) were known to mediate intrinsic immunity against HCMV. In this study, we identify the chromatin modulator SPOC1 as a novel restriction factor against HCMV. We show that preexisting high SPOC1 protein levels mediate a silencing of HCMV gene expression via a specific association with an important viral cis-regulatory element, the major immediate early promoter. Since SPOC1 expression varies between cell types, this factor may play an important role in tissue-specific defense against HCMV.
EVALuna2:34842

Genome-wide cooperation of EMT transcription factor ZEB1 with YAP and AP-1 in breast cancer - Feldker, Nora; Ferrazzi, Fulvia; Schuhwerk, Harald; Widholz, Sebastian A.; Guenther, Kerstin; Frisch, Isabell; Jakob, Kathrin; Kleemann, Julia; Riegel, Dania; Bönisch, Ulrike; Lukassen, Sören; Eccles, Rebecca; et al. (EMBO Journal, 2020)
Invasion, metastasis and therapy resistance are the major cause of cancer-associated deaths, and the EMT-inducing transcription factor ZEB1 is a crucial stimulator of these processes. While work on ZEB1 has mainly focused on its role as a transcriptional repressor, it can also act as a transcriptional activator. To further understand these two modes of action, we performed a genome-wide ZEB1 binding study in triple-negative breast cancer cells. We identified ZEB1 as a novel interactor of the AP-1 factors FOSL1 and JUN and show that, together with the Hippo pathway effector YAP, they form a transactivation complex, predominantly activating tumour-promoting genes, thereby synergising with its function as a repressor of epithelial genes. High expression of ZEB1, YAP, FOSL1 and JUN marks the aggressive claudin-low subtype of breast cancer, indicating the translational relevance of our findings. Thus, our results link critical tumour-promoting transcription factors: ZEB1, AP-1 and Hippo pathway factors. Disturbing their molecular interaction may provide a promising treatment option for aggressive cancer types.
CRIS-Team Scopus Importer:2020-07-31
Keywords: AP-1; breast cancer; epithelial to mesenchymal transition; ZEB1

Genome-wide cooperation ofEMTtranscription factorZEB1 withYAPandAP-1 in breast cancer - Feldker, Nora; Ferrazzi, Fulvia; Schuhwerk, Harald; Widholz, Sebastian A.; Guenther, Kerstin; Frisch, Isabell; Jakob, Kathrin; Kleemann, Julia; Riegel, Dania; Boenisch, Ulrike; Lukassen, Sören; Eccles, Rebecca; et al. (EMBO Journal, 2020)
Invasion, metastasis and therapy resistance are the major cause of cancer-associated deaths, and theEMT-inducing transcription factorZEB1 is a crucial stimulator of these processes. While work onZEB1 has mainly focused on its role as a transcriptional repressor, it can also act as a transcriptional activator. To further understand these two modes of action, we performed a genome-wideZEB1 binding study in triple-negative breast cancer cells. We identifiedZEB1 as a novel interactor of theAP-1 factorsFOSL1 andJUNand show that, together with the Hippo pathway effectorYAP, they form a transactivation complex, predominantly activating tumour-promoting genes, thereby synergising with its function as a repressor of epithelial genes. High expression ofZEB1,YAP,FOSL1 andJUNmarks the aggressive claudin-low subtype of breast cancer, indicating the translational relevance of our findings. Thus, our results link critical tumour-promoting transcription factors:ZEB1,AP-1 and Hippo pathway factors. Disturbing their molecular interaction may provide a promising treatment option for aggressive cancer types.
CRIS-Team WoS Importer:2020-09-25

Hobit- and Blimp-1-driven CD4(+) tissue-resident memory T cells control chronic intestinal inflammation - Zundler, Sebastian; Becker, Emily; Spocinska, Marta; Slawik, Monique; Parga-Vidal, Loreto; Stark, Regina; Wiendl, Maximilian; Atreya, Raja; Rath, Timo; Leppkes, Moritz; Hildner, Kai; Lopez Posadas, Rocío; et al. (Nature Immunology, 2019)
Although tissue-resident memory T cells (T-RM cells) have been shown to regulate host protection in infectious disorders, their function in inflammatory bowel disease (IBD) remains to be investigated. Here we characterized T-RM cells in human IBD and in experimental models of intestinal inflammation. Pro-inflammatory T-RM cells accumulated in the mucosa of patients with IBD, and the presence of CD4(+)CD69(+)CD103(+) T-RM cells was predictive of the development of flares. In vivo, functional impairment of T-RM cells in mice with double knockout of the T-RM-cell-associated transcription factors Hobit and Blimp-1 attenuated disease in several models of colitis, due to impaired cross-talk between the adaptive and innate immune system. Finally, depletion of T-RM cells led to a suppression of colitis activity. Together, our data demonstrate a central role for T-RM cells in the pathogenesis of chronic intestinal inflammation and suggest that these cells could be targets for future therapeutic approaches in IBD.
CRIS-Team WoS Importer:2019-03-06

Inflammation-induced glycolytic switch controls suppressivity of mesenchymal stem cells via STAT1 glycosylation - Jitschin, R.; Böttcher, Martin; Saul, D.; Lukassen, Sören; Bruns, Heiko; Loschinski, Romy; Ekici, Arif Bülent; Reis, André; Mackensen, Andreas; Mougiakakos, Dimitrios (Leukemia, 2019)
Mesenchymal stem cells (MSCs) represent key contributors to tissue homeostasis and promising therapeutics for hyperinflammatory conditions including graft-versus-host disease. Their immunomodulatory effects are controlled by microenvironmental signals. The MSCs' functional response towards inflammatory cues is known as MSC-"licensing" and includes indoleamine 2,3-dioxygenase (IDO) upregulation. MSCs use tryptophan-depleting IDO to suppress T-cells. Increasing evidence suggests that several functions are (co-)determined by the cells' metabolic commitment. MSCs are capable of both, high levels of glycolysis and of oxidative phosphorylation. Although several studies have addressed alterations of the immune regulatory phenotype elicited by inflammatory priming metabolic mechanisms controlling this process remain unknown. We demonstrate that inflammatory MSC-licensing causes metabolic shifts including enhanced glycolysis and increased fatty acid oxidation. Yet, only interfering with glycolysis impacts IDO upregulation and impedes T-cell-suppressivity. We identified the Janus kinase (JAK)/signal transducer and activator of transcription (STAT)1 pathway as a regulator of both glycolysis and IDO, and show that enhanced glucose turnover is linked to abundant STAT1 glycosylation. Inhibiting the responsible O-acetylglucosamine (O-GlcNAc) transferase abolishes STAT1 activity together with IDO upregulation. Our data suggest that STAT1-O-GlcNAcylation increases its stability towards degradation thus sustaining downstream effects. This pathway could represent a target for interventions aiming to enhance the MSCs' immunoregulatory potency.
EVALuna2:35805

In Vivo Protein Complementation Demonstrates Presynaptic α-Synuclein Oligomerization and Age-Dependent Accumulation of 8–16-mer Oligomer Species - Kiechle, Martin; von Einem, Bjoern; Höfs, Lennart; Voehringer, Patrizia; Grozdanov, Veselin; Markx, Daniel; Parlato, Rosanna; Wiesner, Diana; Mayer, Benjamin; Sakk, Olena; Baumann, Bernd; Lukassen, Sören; et al. (Cell Reports, 2019)
Kiechle et al. present two transgenic mouse models that allow direct quantitative and spatial detection of α-synuclein (α-syn) oligomers in vivo. They demonstrate α-syn aggregation at the synapse, age-dependent accumulation of 8–16-mer α-syn oligomer species, and trans-cellular oligomer spreading from forebrain to hindbrain neurons.
CRIS-Team Scopus Importer:2019-12-03
Keywords: aging; alpha-synuclein; neurodegeneration; oligomerization; Parkinson's disease; progressive phenotype; protein-fragment complementation; spreading; synaptic oligomers; transgenic mouse model

Lymphocyte Immune Response and T Cell Differentiation in Fontan Patients with protein-losing enteropathy - Moosmann, Julia; Toka, Okan; Lukassen, Sören; Ekici, Arif Bülent; Mackensen, Andreas; Dittrich, Sven; Völkl, Simon (Thoracic and Cardiovascular Surgeon, Supplement, 2021)
Background Protein-losing enteropathy (PLE) is a severe complication of the Fontan circulation. There is increasing discussion about whether lymphatic dysregulation is involved as pathomechanism of PLE. This investigation focuses on the interplay between alteration of lymphatic cells and immunologic pathway alterations. Methods Micro-ribonucleic acid (miRNA) expression profiling was performed in 49 patients (n = 10 Fontan patients with PLE, n = 30 Fontan patients without PLE, and n = 9 patients with dextro-transposition of the great arteries (dTGA). miRNA pathway analysis was performed to identify significantly enriched pathways. To determine lymphocyte populations and subtypes multiparameter flow cytometry was used. Results miRNAs pathway analysis of Fontan patients with PLE revealed 20 significantly changed networks of which four of the ten largest were associated with immunologic processes. This finding is supported by significant T cell deficiency with decreased CD4+ count (p = 0.0002), altered CD4 +/CD8+ ratio, and significantly modified CD4+ (p < 0.0001) and CD8+ (p = 0.0002) T cell differentiation toward effector and terminal differentiated T cells in Fontan patients with PLE. Analyses of CD4+ T cell subsets demonstrated significantly increased frequencies of CD4+ CD25+ CD127- regulatory T cells (Treg) in Fontan patients with PLE (p = 0.0011). Conclusion PLE in Fontan patients is associated with severe lymphopenia, T cell deficiency, significant alterations of T cell differentiation, and increased Treg frequency reflecting an immune status of chronic inflammation and shortened protection against pathogens and autoimmunity. These cellular alterations seemed to be dysregulated by several miRNA controlled immunological pathways.
CRIS-Team Scopus Importer:2021-03-05
Keywords: congenital heart disease (CHD); genetics; genomics; inflammation; systemic

PEDF Is Associated with the Termination of Chondrocyte Phenotype and Catabolism of Cartilage Tissue - Klinger, Patricia; Lukassen, Sören; Ferrazzi, Fulvia; Ekici, Arif Bülent; Hotfiel, Thilo; Swoboda, Bernd; Aigner, T.; Gelse, Kolja (BioMed Research International, 2017)
Objective. To investigate the expression and target genes of pigment epithelium-derived factor (PEDF) in cartilage and chondrocytes, respectively. Methods. We analyzed the expression pattern of PEDF in different human cartilaginous tissues including articular cartilage, osteophytic cartilage, and fetal epiphyseal and growth plate cartilage, by immunohistochemistry and quantitative real-time (qRT) PCR. Transcriptome analysis after stimulation of human articular chondrocytes with rhPEDF was performed by RNA sequencing (RNA-Seq) and confirmed by qRT-PCR. Results. Immunohistochemically, PEDF could be detected in transient cartilaginous tissue that is prone to undergo endochondral ossification, including epiphyseal cartilage, growth plate cartilage, and osteophytic cartilage. In contrast, PEDF was hardly detected in healthy articular cartilage and in the superficial zone of epiphyses, regions that are characterized by a permanent stable chondrocyte phenotype. RNA-Seq analysis and qRT-PCR demonstrated that rhPEDF significantly induced the expression of a number of matrix-degrading factors including SAA1, MMP1, MMP3, and MMP13. Simultaneously, a number of cartilage-specific genes including COL2A1, COL9A2, COMP, and LECT were among the most significantly downregulated genes. Conclusions. PEDF represents a marker for transient cartilage during all neonatal and postnatal developmental stages and promotes the termination of cartilage tissue by upregulation of matrix-degrading factors and downregulation of cartilage-specific genes. These data provide the basis for novel strategies to stabilize the phenotype of articular cartilage and prevent its degradation.
EVALuna2:9364

Single-cell RNA sequencing of adult mouse testes - Lukassen, Sören; Bosch, Elisabeth; Ekici, Arif Bülent; Winterpacht, Andreas (Scientific Data, 2018)
Spermatogenesis is an efficient and complex system of continuous cell differentiation. Previous studies investigating the transcriptomes of different cell populations in the testis relied either on sorting cells, cell depletion, or juvenile animals where not all stages of spermatogenesis have been completed. We present single-cell RNA sequencing (scRNA-Seq) data of 2,500 cells from the testes of two 8-week-old C57Bl/6J mice. Our dataset includes all spermatogenic stages from preleptotene to condensing spermatids as well as individual spermatogonia, Sertoli and Leydig cells. The data capture the full continuity of the meiotic and postmeiotic stages of spermatogenesis, and is thus ideally suited for marker discovery, network inference and similar analyses for which temporal ordering of differentiation processes can be exploited. Furthermore, it can serve as a reference for future studies involving single-cell RNA-Seq in mice where spermatogenesis is perturbed.
EVALuna2:34826